Upaya Indonesia Meningkatkan Pariwisata Maritim melalui Diplomasi Kebudayaan di Asia Tenggara - Dwi W., Harits; Subekti N., Bagus (Indonesian Perspective, 2017)
Indonesia is one of the largest archipelagic countries in the world, having more than 17,000 islands. It becomes one priority to the state building, more importantly in the national economy. State economic development can be driven by maximizing the potential of seawater through the tourism industry, especially in maritime tourism which is one part of the third pillars of the maritime axis. Maritime tourism may serve as an instrument of Indonesian diplomacy to compete in Southeast Asia’s tourism race. It could be very significant when the government is able to manage the potential resources. This paper argues that maritime tourism is potential for Indonesian development through maritime tourism industry in the future. This paper employs cultural diplomacy concept to describe how cultural diplomacy plays role as an instrument in promoting Indonesia’s tourism industry in the region.Keywords: maritime tourism, cultural diplomacy, tourism industry